An Assessment of the Investment Climate in Nigeria - Iarossi, Giuseppe; Mousley, Peter; Radwan, Ismail (World Bank, 2012)
Nigeria's vision of 2020 is a bold desire to be among the top twenty economies by the year 2020. The economy has posted impressive growth figures since 2003 driven by higher oil prices and a series of home-grown, economic reforms. The country is now firmly on the road to middle-income status. This Investment Climate Analysis is built on a 2,300 firm survey and provides evidence-based recommendations designed to support the vision 2020. Survey results represent investment climate status in Nigeria and are grouped by the following topics: firm productivity and business environment, comparison of state level investment climates, access to finance, entrepreneurship and managerial capacity in firms, and investment climate aspects. The authors conclude that stakeholder consultations on the diagnostic work, policy assessment, and design would improve Nigeria's investment climate.